THE DEVELOPMENT OF BASIC CHEMISTRY PRACTICAL GUIDE-BOOK OF SCIENTIFIC APPROACH TO DEVELOP COLLEGE STUDENTS SCIENTIFIC THINKING SKILLS - Rahmat Rasmawan (Jurnal Pengajaran MIPA, 2019)
This research aims to develop a practical guide-book of scientific approach that can develop college students scientific thinking skills. The research is using the Research and Development (R D) form by follow development path of ADDIE (Analyze Design, Develop, implement and Evaluate). The result of validation from the education and the chemistry experts showed that the practical guide-book that where develop was valid and possible to use. Then the practical guide-book is implemented into learning and the results showed that there are differences in students' scientific thinking skills before and after the developed practical guide-book are implemented and there is an increase with a normal gain score is 0.76 which is in the high category and students respond positively to practical activities using scientific-based practical guide-book. Thus it can beconcluded that the developed practical guide-book  is valid and possible to use and can develop students' scientific thinking skills